2008
DOI: 10.2332/allergolint.o-07-514
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double-Blind Comparative Study of Sublingual Immunotherapy for Cedar Pollinosis

Abstract: SLIT was effective and safe in the treatment of cedar pollinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 24 publications
1
42
1
Order By: Relevance
“…A randomized double-blind study reported that efficacy variable scores in an active treatment group were significantly lower than those in a placebo group, and the quality of life (QOL) symptom score of the active group was almost half that of the placebo group [3]. We also previously reported that active treatment significantly ameliorated symptom scores and symptom-medication scores compared with placebo in a randomized controlled trial.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A randomized double-blind study reported that efficacy variable scores in an active treatment group were significantly lower than those in a placebo group, and the quality of life (QOL) symptom score of the active group was almost half that of the placebo group [3]. We also previously reported that active treatment significantly ameliorated symptom scores and symptom-medication scores compared with placebo in a randomized controlled trial.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, two reports have described the positive clinical effects of sublingual immunotherapy (SLIT) against Japanese cedar pollinosis [3,4]. A randomized double-blind study reported that efficacy variable scores in an active treatment group were significantly lower than those in a placebo group, and the quality of life (QOL) symptom score of the active group was almost half that of the placebo group [3].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Currently SIT may be administered as subcutaneous (SCIT) or sublingual (SLIT). SLIT appears to be associated with lower incidence of systemic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the total pollen count in Chiyoda Ward of Tokyo (the closest location to Nippon Medical School hospital) was approximately 1250/cm 2 by the Durham method. In 2005, Okubo et al [13] investigated SLIT for cedar pollen allergy using a symptom diary to determine scores for symptoms. The pollen count was high that year and the total pollen count in Chiyoda Ward was 10625/cm 2 .…”
Section: Igg4/iggmentioning
confidence: 99%